Cadmium-Induced Tubular Dysfunction in Type 2 Diabetes: A Population-Based Cross-Sectional Study - Soisungwan Satarug; Supabhorn Yimthiang; Phisit Pouyfung; Tanaporn Khamphaya; David A. Vesey (Toxics, 2023)
The global prevalence of diabetes, and its major complication, diabetic nephropathy, have reached epidemic proportions. The toxic metal cadmium (Cd) also induces nephropathy, indicated by a sustained reduction in the estimated glomerular filtration rate (eGFR) and the excretion of β2-microglobulin (β2M) above 300 µg/day, which reflects kidney tubular dysfunction. However, little is known about the nephrotoxicity of Cd in the diabetic population. Here, we compared Cd exposure, eGFR, and tubular dysfunction in both diabetics (n = 81) and non-diabetics (n = 593) who were residents in low- and high-Cd exposure areas of Thailand. We normalized the Cd and β2M excretion rates (ECd and Eβ2M) to creatinine clearance (Ccr) as ECd/Ccr and Eβ2M/Ccr. Tubular dysfunction and a reduced eGFR were, respectively, 8.7-fold (p < 0.001) and 3-fold (p = 0.012) more prevalent in the diabetic than the non-diabetic groups. The doubling of ECd/Ccr increased the prevalence odds ratios for a reduced eGFR and tubular dysfunction by 50% (p < 0.001) and 15% (p = 0.002), respectively. In a regression model analysis of diabetics from the low-exposure locality, Eβ2M/Ccr was associated with ECd/Ccr (β = 0.375, p = 0.001) and obesity (β = 0.273, p = 0.015). In the non-diabetic group, Eβ2M/Ccr was associated with age (β = 0.458, p < 0.001) and ECd/Ccr (β = 0.269, p < 0.001). However, after adjustment for age, and body mass index (BMI), Eβ2M/Ccr was higher in the diabetics than non-diabetics of similar ECd/Ccr ranges. Thus, tubular dysfunction was more severe in diabetics than non-diabetics of similar age, BMI, and Cd body burden.